The Effectof giving Tubifex sp dan Frozen Bloodworms (Chironomus sp Larvae) on Growth dan Survival rate ofSheetfishLarvae(Ompok rhadinurus) - Candra Setiawan; Hamdan Alawi; Netty Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The aim of this study was to evaluate the effect offeed types of fresh Tubifex worm, frozen Tubifex worm, mixed Tubifex (fresh and frozen) and frozen blood worms on the growth of survival of sheetfish larvae and to know the best type of feed between frozen Tubifex sp and frozen blood worms which can be used as an initial feed for sheetfish larvae other than fresh Tubifex sp reared in a recirculation system. This experiment used Completely Random Design (CRD) with 4 treatments and 3 replications, namely P1: feeding the fresh Tubifex, P2: feeding the frozen Tubifex, P3: feeding the frozen blood worms, P4: Feeding the combination feed (fresh and frozen) with frozen blood worms. The results showed that there was an effect of feeding Tubifex sp and frozen blood worms on the growth and survival of sheetfish fish larvae (Ompok rhadinurus). The best treatment, P1with fresh Tubifex sp which produces an average growth of absolute weight of 5,14 grams, absolute length 8,76 cm, growth rate of 14,95% / day weight and 100% survival. Water quality parameter values are temperature of 270C - 280C, pH 5,6-5,7 and dissolved oxygen (DO) between 3,3-6,0 mg/l. Keywords : Tubifexsp, frozen blood worms, ikan selais (Ompok rhadinurus).